Infant Eye Gaze While Viewing Dynamic Faces - Lisa M. Oakes; Michaela C. DeBolt; Aaron G. Beckner; Annika T. Voss; Lisa M. Cantrell (Brain Sciences, 2021)
Research using eye tracking methods has revealed that when viewing faces, between 6 to 10 months of age, infants begin to shift visual attention from the eye region to the mouth region. Moreover, this shift varies with stimulus characteristics and infants’ experience with faces and languages. The current study examined the eye movements of a racially diverse sample of 98 infants between 7.5 and 10.5 months of age as they viewed movies of White and Asian American women reciting a nursery rhyme (the auditory component of the movies was replaced with music to eliminate the influence of the speech on infants’ looking behavior). Using an analytic approach inspired by the multiverse analysis approach, several measures from infants’ eye gaze were examined to identify patterns that were robust across different analyses. Although in general infants preferred the lower regions of the faces, i.e., the region containing the mouth, this preference depended on the stimulus characteristics and was stronger for infants whose typical experience included faces of more races and for infants who were exposed to multiple languages. These results show how we can leverage the richness of eye tracking data with infants to add to our understanding of the factors that influence infants’ visual exploration of faces.